CLINICAL-EPIDEMIOLOGICAL PROFILE OF PATIENTS WITH DIAGNOSIS OF ORAL CAVITY CANCER - Isabella Souza Santos, Lara; Silveira de Oliveira, Isabela; Melo Ribeiro, Marina; Faustino de Souza, Lucas; Maria Alencar, Ana; Cruz Dias, Talita; Lira Santos Ribeiro, Bruna (Health and Society, 2021)
Introduction: Cancer of the oral cavity is a malignant tumor that can occur in the lips, oral structures and region under the tongue. They are cancers that often affect male patients aged 40 years and over. Objective: To describe the clinical and epidemiological profile of patients diagnosed with oral cavity cancer from 2015 to 2019 in Montes Claros, Minas Gerais, Brazil. Methods: A descriptive study of quantitative approach was conducted through data from patients living in Montes Claros, Minas Gerais with diagnosis of oral cavity neoplasia in hospital records of the José Alencar Gomes da Silva National Cancer Institute (INCA). Results and discussion: In the historical series analyzed, 312 cases of cancer of the oral cavity were identified. Conclusion: The patients who were diagnosed with cancer in the oral cavity were mostly men aged between 50 and 69 years, the association between concomitant use of tobacco and alcoholic beverages was present in the vast majority of cases. Health professionals’ efforts are needed for early diagnosis through educational actions and primary prevention.